ASUHAN KEBIDANAN NIFAS PADA NY. “D” 6 JAM POST PARTUM DI BPM NY. HARTINI DESA REBALAS KABUPATEN PASURUAN - Anggreni, Dhonna; Renita Widya Wahyuni (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2022)
The puerperium is a critical period and has the potential for complications after childbirth. It is estimated that 60% of maternal deaths in Indonesia occur during the puerperium, and 50% of postpartum deaths occur in the first 24 hours. The purpose of this study was to provide midwifery care to mothers 6 hours post partum. This type of research is a case study by providing midwifery care to postpartum mothers. This study was conducted with midwifery management and documentation using SOAP. The sample in this study Mrs. D, age 25 years with normal delivery. The research was conducted at BPM Ny. Hartini, Relaba Village, Grati District, Pasuruan. The results showed that P10001 mother 6 hours post partum. Mother complains of pain in the lower abdomen and pain in the perineal wound, all of which are physiological. After being given midwifery care, the mother understood the explanation given and promised to carry out all the recommendations. It is recommended to health workers and families to always provide support to postpartum mothers. Because at this time not only physical changes occur in the mother, but also psychological and social changes. So that the mother can experience the postpartum period comfortably and safely